Europe and Asia
XVI, 213 p.
Keywords: Much more than a simple examination of EU-Asia relations, this book examines the idea that the EU may constitute a 'model' for East Asian regionalism. It challenges specialists on the EU to understand the EU's impact on Asia and Asia's impact on the EU whilst illustrating that there is a commonality of interests in both Europe and Asia.